The interaction between blood lipids and ASCVD increases the risk of DKD: a nonlinear relationship transforms into a linear relationship, a cross-sectional study - Li, Huan; Shi, Yulu; Zhang, Hui; Han, Jie; Zhang, Xiaoping; Liu, ZiJie (Frontiers in Endocrinology, 2025)
BackgroundAtherosclerotic cardiovascular disease (ASCVD) and diabetic kidney disease (DKD) are interconnected vascular complications in diabetes, with dyslipidemia playing a key role. The modifying effect of ASCVD on the lipid-DKD relationship in diabetic patients without lipid-lowering treatment remains unclear.MethodsThis retrospective study included 26,476 type 2 diabetic patients without lipid-lowering therapy. Associations between lipids (LDL-C, TC, TG, HDL-C) and DKD risk were analyzed using regression and restricted cubic spline (RCS) curves analysis. Both multiplicative and additive interactions between lipids and ASCVD were assessed.ResultsHDL-C showed a significant linear association with DKD. RCS analyses revealed distinct patterns based on ASCVD status: significant threshold effects for LDL-C (2.68 mmol/L), TC (4.29 mmol/L), TG (2.48 mmol/L), and HDL-C (1.64 mmol/L) on DKD risk were observed only in diabetic patients without ASCVD. No significant nonlinear threshold effects were found for LDL-C, TC, HDL-C on DKD risk in diabetic patients with ASCVD. LDL-C and TC showed continuous increases in DKD risk without a discernible safe threshold in diabetic patients with ASCVD. Crucially, a strong synergistic interaction existed between ASCVD and both TC (RERI=7.46, AP=0.25, SI=1.34) and LDL-C (RERI=9.91, AP=0.27, SI=1.38), significantly amplifying their adverse effects on renal injury.ConclusionASCVD amplifies the detrimental renal effects of TC and LDL-C and eliminates protective lipid thresholds in diabetic patients. Consequently, lipid management in diabetic patients should be individualized: strict control of TC and LDL-C is prioritized for those with ASCVD, while consideration of lipid threshold effects is key for those without ASCVD.